People's Republic of China : Spillover Report for the 2011 Article IV Consultation and Selected Issues. (IMF Staff Country Reports; Country Report ;, 2011)
The Chinese authorities welcomed the spillover analysis, noting that their policies have important global spillover effects. The note also discusses China's evolving role in global trade, impact of rebalancing on the supply chain, estimating China's spillovers, elasticities approach, factor pricing, overcapacity, and sustainability risks. It elaborates on the impact of competition from Brazil and Mexico, China's closed capital account and capital flows to emerging markets, the impact of China's saving on global financial conditions, and potential impact on global bond markets of reallocating reserves.